Is more always better? An examination of the nonlinear effects of perceived organizational support on individual outcomes. Issue 2 (4th March 2018) - Harris, Kenneth J.; Kacmar, K. Michele
ABSTRACT: A wide range of research has accumulated detailing the positive associations of perceived organizational support (POS) with desirable workplace outcomes (e.g., high performance, high commitment, low deviance). In the process, there has been an implicit assumption that these relationships are linear, with ever-increasing POS resulting in ever-increasing positive outcomes. However, there are theoretical and practical reasons to question whether these relationships may be nonlinear rather than linear. Our results offer support for the notion that the relationships between POS and key individual outcomes rated by the supervisor may best be represented as nonlinear. We conclude by highlighting the implications for both theory and practice.